2003
DOI: 10.3139/146.030411
|View full text |Cite
|
Sign up to set email alerts
|

The Fe–Cr–Zn System in Relation with the Galvanizing Process in Chromium-Added Zinc Bath

Abstract: The Fe-Cr-Zn system in relation with the galvanizing process in chromium-added zinc bathTaking into account new experimental measurements, the Fe -Zn -Cr ternary system is critically modified at 460°C. A continuous solid solution between f-FeZn 13 and CrZn 13 compounds is shown but is shared at 460°C by the stable CrZn 17 compound containing about 2 wt.% Fe. This ternary system is assessed with the CALPHAD method using the PARROT modulus of the Thermo-Calc software. The liquid and solid solution phases are mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It was reported that information on the Al-Fe-Zn system had been effectively applied to the galvanizing industry for the determination of effective Al content in the molten bath, the management of the dross generation and the prediction of the Al consumption [2]. Several galvanizing-related alloy systems, such as Fe-Ni-Zn [3], Fe-Sn-Zn [4], Fe-Ti-Zn [5], Al-Fe-Zn [6], Fe-Mn-Zn [7], Cr-Fe-Zn [8], Bi-Ni-Zn [9] and Al-Mo-Zn [10], were experimentally investigated. In addition, the phase equilibria in some quaternary systems, such as Zn-Fe-Ni-Ti [11] and Zn-Fe-Ni-Si [12], were also experimentally studied.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that information on the Al-Fe-Zn system had been effectively applied to the galvanizing industry for the determination of effective Al content in the molten bath, the management of the dross generation and the prediction of the Al consumption [2]. Several galvanizing-related alloy systems, such as Fe-Ni-Zn [3], Fe-Sn-Zn [4], Fe-Ti-Zn [5], Al-Fe-Zn [6], Fe-Mn-Zn [7], Cr-Fe-Zn [8], Bi-Ni-Zn [9] and Al-Mo-Zn [10], were experimentally investigated. In addition, the phase equilibria in some quaternary systems, such as Zn-Fe-Ni-Ti [11] and Zn-Fe-Ni-Si [12], were also experimentally studied.…”
Section: Introductionmentioning
confidence: 99%
“…Reumont and Perrot [4] reassessed this partial phase diagram and included the CrZn13 phase as well. The partial phase diagram was subsequently accepted in the related higher order systems [14][15][16][17][18][19]. However, the stability of CrZn13 was questioned by Hansen [6] from the very beginning.…”
Section: Literature Datamentioning
confidence: 99%
“…Nevertheless, a few difficulties have been encountered while galvanizing such AHSS because of the high alloy chemistry of the substrate [2]. High silicon concentration in martensitic steel could modify the reactivity in the bath due to the Sandelin effect [3], Mn tends to form MnO at the external steel surface during continuous annealing prior hot-dipping [4], and Cr could also form specific intermetallic compounds (IMCs) [5][6][7][8][9]. The formation, transformation, and growth of IMCs in interfacial reaction and post-treatment process crucially determine the interfacial properties of coating and thus the mechanical reliability of galvanized AHSS products.…”
Section: Introductionmentioning
confidence: 99%
“…By dipping three starting materials, Fe, Cr, and Fe-77 wt.% Cr in a molten Zn bath containing 0.71 wt.% Cr at 460°C up to 16 h, Reumont et al [5] identified a ternary phase ζ′ having a Cr content of 2-5.5 wt.% and a Zn content of~93-95 wt.%, and it was in equilibrium with ζ-FeZn 13 , CrZn 17 , CrZn 13 and liquid phase in the Zn-rich corner. Tang et al [6] equilibrated Fe-Cr-Zn molted alloys in a ceramic crucible between 470 and 430°C at~10°C intervals.…”
Section: Introductionmentioning
confidence: 99%